Implementation of VPN Using the PPTP Method to Access CCTV Monitoring Data at the Bukit Raya District Office - Tiara Dwi Kharisma (INOVTEK Polbeng - Seri Informatika, 2024)
Bukit Raya District faces challenges in monitoring activities across five scattered sub-districts, as well as employees frequently being absent from the office during working hours. To address this issue, the installation of a CCTV system is crucial for monitoring employee performance and office activities. However, remote access to CCTV data is not yet available. This study aims to implement a VPN using the PPTP (Point to Point Tunneling Protocol) method to allow CCTV monitoring data in sub-district offices to be securely and stably accessed from the district office. PPTP was chosen due to its cross-platform support and ease of configuration and maintenance. The implementation was carried out in two sub-districts, Tangkerang Selatan and Simpang Tiga. The results indicate that the PPTP VPN successfully connected the district office to these sub-districts, enabling secure remote access to CCTV data. Quality of Service (QoS) testing demonstrated network performance improvements in terms of throughput, packet loss, delay, and jitter. Therefore, this system effectively enhances operational efficiency and security in Bukit Raya District.